2012
DOI: 10.1890/11-0825.1
|View full text |Cite
|
Sign up to set email alerts
|

Advertising to the enemy: enhanced floral fragrance increases beetle attraction and reduces plant reproduction

Abstract: Many organisms face challenges in avoiding predation while searching for mates. For plants, emitting floral fragrances to advertise reproductive structures could increase the attraction of detrimental insects along with pollinators. Very few studies have experimentally evaluated the costs and benefits of fragrance emission with explicit consideration of how plant fitness is affected by both pollinators and florivores. To determine the reproductive consequences of increasing the apparency of reproductive parts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 40 publications
(51 reference statements)
1
82
0
Order By: Relevance
“…2), further suggesting their function in attracting day-active bee pollinators. However, recent studies have drawn attention to the impact of floral enemies as selective agents (Theis and Adler 2012;Theis et al 2007), additionally suggesting that reducing attractive volatiles at night or even increasing the emission of repellent volatiles may be strategies to avoid attracting florivores or predispersal seed predators (Theis 2006). For example, a floral filter function is possible for methyl salicylate, which comprises a larger proportion of the floral blend of P. digitalis at night.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), further suggesting their function in attracting day-active bee pollinators. However, recent studies have drawn attention to the impact of floral enemies as selective agents (Theis and Adler 2012;Theis et al 2007), additionally suggesting that reducing attractive volatiles at night or even increasing the emission of repellent volatiles may be strategies to avoid attracting florivores or predispersal seed predators (Theis 2006). For example, a floral filter function is possible for methyl salicylate, which comprises a larger proportion of the floral blend of P. digitalis at night.…”
Section: Discussionmentioning
confidence: 99%
“…Plants emit a variety of floral volatile compounds (Knudsen et al 2006) enabling them to communicate and interact with mutualist pollinators (Raguso 2008a;Wright and Schiestl 2009) and antagonists, such as florivores ) and herbivores (Kessler and Baldwin 2007;Theis and Adler 2012). However, the chemical composition of floral scent is not static.…”
Section: Introductionmentioning
confidence: 99%
“…Benkman et al 2012;Pauw et al 2009; Toju et al 2011), but studies of chemical diversification increasingly have shown that coevolution is just as often about attractants, repellents, toxic compounds, and counter responses to those compounds (Berenbaum and Zangerl 2006;Brodie and Ridenhour 2003;Ehrlich and Raven 1964;Foitzik et al 2003;Hanifin et al 2008;Johnson et al 2010;Raguso 2008;. Attractants are a particularly intriguing class of compounds in coevolving interactions, because they actively attract mutualists but may simultaneously attract enemies (Theis and Adler 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The production of such a diverse array of compounds is likely to incur energetic (Gershenzon 1994;Wright and Schiestl 2009) and ecological costs, because the same compounds that attract mutualistic insects also may attract antagonistic herbivores and seed predators (Irwin et al 2004;Proffit et al 2007;Schiestl et al 2011;Theis 2006;Theis and Adler 2012;Wright and Schiestl 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally augmenting floral scent increased pollinator attraction for Hesperis matronalis [46], but only with specific components of its floral bouquet. In contrast, a similar experiment with Curcurbita pepo had no effect on pollinators but increased visits from florivores [47]. Similar dynamics can occur with visual cues [48,49] for example the showy bracts of Dalechampia scandens are attractive to both pollinators and seed predators [48].…”
Section: Attracting More Of Whatever Pollinators There Arementioning
confidence: 82%